Assessing the Role of Electronic Banking on Performance of Micro Financial Institutions: A Case Study of Pride Micro Finance Limited Kabale District. - Twagirayesu, Bertin (Kabale University, 2023)
The study was conducted to examine the role of electronic banking on the performance of micro-financial institutions A case study of pride Microfinance limited Kabale district the specific objectives were to analyze the importance of electronic banking methods ll1 micro finance institutions, to examine the types of electronic banking methods adopted in microfinance towards their performance and to find out the relationship between electronic banking on performance of micro-financial institutions. The study used a descriptive research design in which both qualitative and quantitative techniques were used to collect and analyze numerical data. The study population constituted of 65 respondents. A sample size of 56 respondents was selected using purposive and simple random sampling techniques. The study found that The study findings on the importance of electronic banking methods in microfinance institutions. the results were obtained from; a digital signature for security. convenience way of operating banking transactions, faster transfer, reliability, and time factor. the study went ahead to find the types of electronic banking methods adopted in microfinance towards their performance and the responses were obtained from mobile/SMS banking. electronic funds transfers. self Service (PC) banking, POS Banking (Credit and Debit cards), internet banking, and an automated teller machine the study findings on the relationship between electronic banking on the performance of microfinance institutions, the results revealed that there is a very high positive significant relationship between electronic banking on the performance of microfinance institutions that is 0.853 significant at 0.0I level of a two-tailed test with 50 degrees of freedom. It was concluded that electronic banking is of great importance in microfinance institutions. The study recommended that there should be awareness among the Microfinance members about the information and communication infrastructure available to enable them to know how they are used to achieve their objectives, the systems used in banking should be in good working conditions and trustable to enable the members use them effectively and there should be constant system check up to avoid systems failures which would disrupt the use of the system in banking operations by the Microfinance clients.